HIV Increases the Risk of Cigarette Smoke-Induced Emphysema Through MMP-9. (1st March 2023) - Staitieh, Bashar S.; Malik, Simran; Auld, Sara C.; Wigger, Gregory W.; Fan, Xian; Roth, Andrew T.; Chatterjee, Tanima; Arora, Itika; Raju, S. Vamsee; Heath, Sonya; Aggrawal, Saurabh
Abstract : Background: HIV is associated with an increased risk for emphysema. Matrix metalloproteinase 9 (MMP-9) is a lung tissue remodeling enzyme associated with emphysema. We previously found MMP-9 activity increases with increases in oxidative stress and that HIV increases alveolar oxidative stress. We hypothesized that HIV proteins would increase the risk of cigarette smoke-induced emphysema due to MMP-9. Methods: HIV-1 transgenic rats and wild-type littermates were exposed to cigarette smoke or sham for 8 weeks. Lung compliance and histology were assessed. Bronchoalveolar lavage (BAL), primary alveolar macrophages (AM), and serum samples were obtained. A rat alveolar macrophage cell line was exposed to the HIV protein Tat, and MMP-9 levels were assessed by Western immunoblotting. MMP-9 protein expression and activity were assessed in AM from the HIV rat model by ELISA and cytoimmunofluoresence, respectively. Serum from human subjects with and without HIV and tobacco dependence was assessed for MMP-9 levels. Results: MMP-9 expression was significantly increased in rat alveolar macrophages after Tat exposure. HIV-1 transgenic rats developed emphysema while wild-type littermates did not. MMP-9 expression was also increased in the serum, BAL, and AM of HIV-1 transgenic rats after exposure to cigarette smoke compared with wild-type rats. In parallel, serum samples from HIV+ smokers had higher levels of MMP-9 than subjects without HIV and those who did not smoke. Conclusion: The combination of HIV and cigarette smoke increases MMP-9 expression in experimental rat HIV models and human subjects. HIV and cigarette smoke both induce alveolar oxidative stress and thereby increase MMP-9 activity.